THE EFFICIENCY ASSESSMENT METHODS OF MANAGEMENT SYSTEM UNDER MANAGEMENT PROCESSES REENGINEERING AT AN ENTERPRISE - R. B. Gamidullaev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The efficiency assessment methods of management system under management processes reengineering at an enterprise. This paper stipulates Necessity and an attempt to assess the system efficiency under management processes reengineering at an enterprise has been made as well. A list of challenges and requirements is given to which the methods of management system efficiency of an enterprise should meet.